The Cloud or Objects Existed in Their Nothingness or Absolute Fiction in the theory of Ibn ʿArabī and its relevance to the Western and Eastern Theories - Shamsud, Professor Dr Salahuddin Bin Mohd; Seman, H. Mohammad b.; Sapar, Ahmad Arifin (IJRDO - Journal of Social Science and Humanities Research, 2018)
First, we say that the cloud is generated from the vapors have the elements of heat. Then the air that surrounds the body of cloud is denied. It is the divine breath, caused by a longing movement based on the love to be discovered and emerged. It’s the soles of the divinity - as Ibn ʿArabī says-because it is the closest creature to God as being an object… By this way the cloud is the same divine-self, in which everything has created. Second, we see that the relationship between the divine science and information to Ibn ʿArabī is a love affair confirms the uniformity between the objects fixed and cloud caused by the divine self to vent the longing to emerge. The fixed objects are found in this cloud as being the realities of the world and its foundation. If the cloud - as we shall see soon - is the absolute fiction, it is natural that Ibn ʿArabī unites - also - between the objects fixed and absolute imagination as being the assets in the ranking of the fantasy existence as being the existential mediator between the divine and the world or between Being and Nothingness. (1)